Pengaruh Penggunaan E-Learning pada Mahasiswa - Mohzana Mohzana; Muhammad Fahrurrozi; Hary Murcahyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
E-learning has been widely used in educational settings especially in developing countries such as Indonesia. The purpose of this study was to investigate e-learning readiness among students and compare students' perceptions of student workloads including mental, physical, temporal, performance, effort, and frustration conditions. in the settings of e-learning and regular lectures.Quantitative methods were used in this study. Using survey techniques with data instruments in the form of questionnaires from 51 data samples. The survey was conducted with students of the Faculty of Arts and Humanities of Hamzanwadi University. Data analysis techniques using NASA-TLX applications. The results showed that students have a high level of e-learning readiness. Mental workloads are significantly higher in e-learning than in face-to-face learning. The correlation between e-learning readiness and mental workload is insignificant. The conclusion of this research is the high readiness of e-learning students because most already have technical skills while the lowest readiness in learning behavior when using e-learning. Student workloads including mental, physical, temporal, performance, effort, and frustration are higher at the time of e-learning use than regular lectures. Keywords: e-learning; workload; Performance